Warm Hearts Day - Elliott, Rebecca (New York : Scholastic Inc., 2016)
Warm Hearts Day is approaching and Eva has been making lots of fun gifts and treats for her friends, but as the big party at the Old Oak Tree nears, she realizes that she has neglected to make any gifts for her family.
2.3
K-3
570L
Keywords: Owls -- Fiction; Holidays -- Fiction; Gifts -- Fiction; Friendship -- Fiction; Owls -- Fiction; Holidays -- Fiction; Gifts -- Fiction; Friendship -- Fiction